2017
DOI: 10.1007/8904_2017_10
|View full text |Cite
|
Sign up to set email alerts
|

Galactose Epimerase Deficiency: Expanding the Phenotype

Abstract: Galactose epimerase deficiency is an inborn error of metabolism due to uridine diphosphate-galactose-4'-epimerase (GALE) deficiency. We report the clinical presentation, genetic and biochemical studies in two siblings with generalized GALE deficiency.Patient 1: The first child was born with a dysmorphic syndrome. Failure to thrive was noticed during the first year. Episodes of heart failure due to dilated cardiomyopathy, followed by liver failure, occurred between 12 and 42 months. The finding of a serum trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…However, a few GALE genetic variants are clearly associated with a mild or severe phenotype. Homozygosity for the variant NM_001008216.2:c.280G > A (p.Val94Met) is associated with a severe phenotype [14]. This is in line with our findings, as 4 of the 6 patients with generalized GALE deficiency were homozygous for this variant.…”
Section: Genotypesupporting
confidence: 91%
See 2 more Smart Citations
“…However, a few GALE genetic variants are clearly associated with a mild or severe phenotype. Homozygosity for the variant NM_001008216.2:c.280G > A (p.Val94Met) is associated with a severe phenotype [14]. This is in line with our findings, as 4 of the 6 patients with generalized GALE deficiency were homozygous for this variant.…”
Section: Genotypesupporting
confidence: 91%
“…However, their long-term outcome is still unclear [9]. The generalized form of GALE deficiency appears to be an extremely rare disorder, with only nine patients (five females and four males) of four families reported in the literature so far [13,14]. In patients with generalized GALE deficiency, the enzyme activity is profoundly decreased in all tissues tested [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[214][215][216] Interestingly,avarietyo fm utations leading to human GalE variants, often with decreased k cat values, have been identified that causet ype III galactosemia [217] and other disorders. [218,219] In addition to its role in the Leloir pathway,G alE is required for the biosynthesis of av ariety of complex polysaccharides andi s an important virulence factor in some Gram-negative pathogens. [216] GalE is ah omodimer with each monomer comprised of an N-terminal nucleotide-bindingd omain containing as evenstranded, parallel b-sheet flankedo ne ither side by six a-helices arranged in am odified Rossmann-like fold, and aC -terminal domain comprised of five b-strands and four a-helices.…”
Section: Udp-galactose4 -Epimerase( Gale)mentioning
confidence: 99%
“…Opisane su dugoročne komplikacije poput poremećaja psihomotoričkog razvoja i učenja, zamjedbenog gubitka sluha i kardiomiopatije. 26,27 Galaktozemija tipa IV uzrokovana je nedostatnom aktivnosti enzima GALM. 2 Procijenjena incidencija široko varira od 1 : 10.000 do 1 : 1.700.000.…”
unclassified